Secondary Metabolite Phytochemical Screening Of Toba Frankincense Leaves (Styrax Paranelonerum Perk) - Ruth Natalia Manurung; Marham Sitorus (Universitas Negeri Medan, 2022)
Toba frankincense plant (Styrax Paralleloneurum PERK) is a native Indonesian plant originating from the west coast of Sumatra, grows naturally and has been widely cultivated. This study aims to identify what secondary metabolites are contained in Toba incense leaves (Styrax Paralleloneurum PERK).